STUDI TENTANG BENTUK DAN PENEMPATAN UKIRAN RUMAH ADAT BUBUNGAN LIMA BENGKULU - Drs. Erfahmi, M.Sn., RIDHO ANANDY, Drs. Efrizal, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2016)
The purpose of the research is description about shape and appointment the design of carved object in tradition house Bubungan Lima Bengkulu. The research method used is avalitative with approacmutdoscri prive. The result of research is inticate shape and placement carved object are source form : 7 motif of flora, fauna 1 motif and geometric 3 motif. The placement of carved object is site in railwaytrack/ fencs / lattice work, post/piabung/bendu and lestplang.Keywords: Form, Placement, Carved Tradition House Bubungan Lima Bengkulu